2022
DOI: 10.1029/2022gb007329
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐Seasonal Forcing Drives Year‐To‐Year Variations of Southern Ocean Primary Productivity

Abstract: Primary productivity in the Southern Ocean plays a key role in global biogeochemical cycles. While much focus has been placed on phytoplankton production seasonality, nonseasonal fluctuations exceed the amplitude of the seasonal cycle across large swaths of the Antarctic Circumpolar Current. This non-seasonal variability comprises a broad range of timescales from sub-seasonal (<3 months) to multi-annual (>1 year), all of which can project onto the annual mean value. However, year-to-year variations of surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 93 publications
2
34
0
Order By: Relevance
“…Events on ∼weekly timescales are likely mechanisms for the short term variability observed in chlorophyll concentration in the ACC, such as mixing events (e.g., storms, eddies, and variability in submesoscale physical dynamics) or biological variability (resulting from nutrient and/or light limitation or grazing). Prend et al (2022) demonstrate that, in the ACC, variations in the annual mean chlorophyll concentration occur over small spatial scales (∼100-300 km; shown with an autocorrelation analysis).…”
Section: Spatial Scales Of Importancementioning
confidence: 81%
See 4 more Smart Citations
“…Events on ∼weekly timescales are likely mechanisms for the short term variability observed in chlorophyll concentration in the ACC, such as mixing events (e.g., storms, eddies, and variability in submesoscale physical dynamics) or biological variability (resulting from nutrient and/or light limitation or grazing). Prend et al (2022) demonstrate that, in the ACC, variations in the annual mean chlorophyll concentration occur over small spatial scales (∼100-300 km; shown with an autocorrelation analysis).…”
Section: Spatial Scales Of Importancementioning
confidence: 81%
“…Previous work has regressed satellite chlorophyll concentration in the Southern Ocean against climate oscillation indices, such as the Southern Annular Mode (SAM), but found limited explanatory power for chlorophyll variability (Prend et al, 2022;see, e.g., Lovenduski & Gruber, 2005). Overall, Prend et al (2022) found that the multi-annual component explained very little of the total chlorophyll variability across most of the Southern Ocean. To investigate why the SAM index has little explanatory power of chlorophyll variability, the authors correlated the SAM index with chlorophyll variability within each temporal component (sub-seasonal, seasonal, and multi-annual).…”
Section: Temporal Scales Of Importancementioning
confidence: 99%
See 3 more Smart Citations